Letter (copy) : Spanish crew
025a-0054-001 Handed by Mr. M. Arenaya COPY. A LUSI LTD. 11 and 12, Bury Street, London, E.C.3. 13th March, 1940. M. Galdeano, Esq., 5, Ensign Street, Cable Street, E.1. Dear Sir, SPANISH CREW. We have your letter of the 8th instant, but regret being unable to agree with your arguments as we never gave you orders either verbally or in writing to keep these men in London at our expense. On the contrary, as nothing was mentioned by you or anybody else on the subject, at any time it seems clear that we cannot be held responsible for expenses which we were never asked to sanction. Our only undertaking was to pay for their travelling expenses and wages as from the date of their departure from London for Havre, had they been allowed to proceed. Further we must complain strongly to you for having engaged the most unsuitable men with the worst possible characters, as the majority of them left the ship before they even had the chance to see her, under various unjustified pretexts and excuses, although they had already received from us, through you £10 in advance on account of their wages. We enclose herewith copy of Captain's letter dated Barry Docks, 12th inst;, from which you will see the facts. We shall place the whole matter in our Solicitors hands in order to get these advances refunded to us and the men prosecuted for the trouble and inconvenience and loss caused to us and the ship. Yours faithfully, (SIGNED) FOR AND ON BEHALF OF A. LUSI LTD. 292/946/25a/54